'I realised I only knew the word partly': student beliefs about vocabulary knowledge and learning in different grades and proficiency levels. Issue 3 (4th May 2023) - Chung, Edsoulla; Fung, Daniel
ABSTRACT: Given the significant role vocabulary plays in second language acquisition, how to help learners acquire vocabulary has always been a concern for educators. Despite the general consensus that beliefs influence learners' behaviour, limited research effort has been devoted to the exploration of English as a second language (ESL) learners' beliefs about vocabulary knowledge and learning in the secondary education context and how their beliefs are affected by such factors as grades and proficiency levels. This paper reports on a convergent mixed-methods study that addresses the research gap with the use of a questionnaire administered to 556 ESL students in a Hong Kong secondary school. Results revealed that while students in general perceived vocabulary learning as important, their beliefs about vocabulary knowledge and learning were found to be related to their grade and proficiency levels. Open-ended responses provided further insights into learners' beliefs qualitatively about the difficulties faced by learners and their perceptions of the effective ways to tackle these difficulties. Overall, this paper broadens the understanding of L2 learners' beliefs about vocabulary knowledge and learning. It complements existing literature on L2 vocabulary learning and sheds light on issues related to vocabulary learning and teaching.